2013
DOI: 10.1177/1099636213509099
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic crushing behavior and energy absorption of honeycombs with density gradient

Abstract: This paper presents an analytical study of the in-plane dynamic crushing and energy absorption of hexagonal honeycombs with density gradients under different impact loading. Explicit dynamic finite element method simulations are carried out by using ANSYS/LS-DYNA. Firstly, under the assumption that the cell wall length is the same, a density-graded honeycomb mode is established by the variation of the cell wall thicknesses along the crushing direction. The effects of density gradient and impact velocity on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 45 publications
0
64
0
Order By: Relevance
“…The quadrature rule is set as Gauss. Numerical results have shown that the shell element is sufficient to produce reliable results [19][20][21][22]29]. Five integration points along the cell-wall thickness are adopted with the aim of providing sufficient accuracy.…”
Section: Finite Element Methods Simulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The quadrature rule is set as Gauss. Numerical results have shown that the shell element is sufficient to produce reliable results [19][20][21][22]29]. Five integration points along the cell-wall thickness are adopted with the aim of providing sufficient accuracy.…”
Section: Finite Element Methods Simulationmentioning
confidence: 99%
“…This is followed by a long collapse plateau and the final compressive densification regime. It is the plateau stress in the second regime that is important in characterizing the dynamic crushing of honeycombs, which has been widely used in the energy-absorbed design and analysis of cellular solid [3,[19][20][21][22][29][30][31]. The plateau stress is defined as the average nominal stress between the first stress peak and the compressive stress corresponding to the densification strain, and its expression is shown as…”
Section: Finite Element Methods Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellular materials, especially cellular sandwich structures, can effectively lighten and strengthen structural component (Wadley, et al, 2003) and also meet multi-functional requirements (Evans, et al, 2001) including energy absorption (Zhu, et al, 2010;Zhang, et al, 2014), shock cushioning (Xue and Hutchinson, 2004), heat dissipation (Queheillalt, et al, 2008) and sound insulation (Xin and Lu, 2010) due to their unique structure configuration.…”
Section: Introductionmentioning
confidence: 99%